2021
DOI: 10.3390/ani11092723
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Determination of Annual Fecal Cortisol, Androstenedione, and Testosterone Variations in a Herd of  Male Asian Elephants (Elephas maximus) and Their Relation to Some Climatic Variables

Abstract: The measurement of stress and reproductive hormones in wild animal species by non-invasive methods is of special interest. To assess whether the adrenal and gonadal hormones show annual variations in male Asian elephants (Elephas maximus) and to evaluate whether there is any influence of climatic variables on hormonal secretion, fecal samples were taken from a herd of 7 Asian elephants over a 14-month period to subsequently determine the concentrations of testosterone (T), androstenedione (A4), and cortisol (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In this study, the number of animals is relatively low, which limits the significance of the results. Since it is a remarkable fact that it is very difficult to find large numbers of a wild species with the behavioral and housing requirements of the white rhinoceroses sharing the same enclosure, many previous studies involving wild species have used a low number of subjects and produced meaningful and insightful findings [ 41 , 42 , 43 , 44 ]. A common practice is that, to increase the number of individuals in a study of wild animals, data from animals housed in different institutions are used [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the number of animals is relatively low, which limits the significance of the results. Since it is a remarkable fact that it is very difficult to find large numbers of a wild species with the behavioral and housing requirements of the white rhinoceroses sharing the same enclosure, many previous studies involving wild species have used a low number of subjects and produced meaningful and insightful findings [ 41 , 42 , 43 , 44 ]. A common practice is that, to increase the number of individuals in a study of wild animals, data from animals housed in different institutions are used [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Brown and colleagues [ 45 ] found no evidence of seasonality in male black and white rhino sex steroid hormones, based on fecal androgen profiles. The authors also reported the independence of cortisol secretion from climatic variables in captive Asian elephants [ 42 ]. Therefore, we believe that climatic conditions may not have an influence on cortisol secretion in white rhinoceroses.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of the fecal EST and TES levels was performed using a competitive EIA that was developed and validated at the Endocrinology Laboratory of the Department of Animal Physiology, Veterinary Faculty, Complutense University of Madrid [15,48]. In summary, similar microtiter plates were coated overnight at 4 A 6957) were prepared by diluting the conjugate stocks in assay buffer.…”
Section: Enzyme Immunoassaysmentioning
confidence: 99%
“…Several studies have developed non-invasive techniques (which limit animal disturbance) to determine the hormonal profiles in order to monitor and improve the management of different animal populations, especially in endangered species [ 7 , 11 , 14 , 15 , 16 , 17 ]. In the rhinoceros, the biological samples used to perform non-invasive hormone assays are feces, urine, and saliva [ 16 , 18 , 19 ]; however, when it comes to wild populations, fecal samples are extensively employed and highly convenient, particularly due to their ease of collection and preservation.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, faecal analysis of food remains represents a useful non-invasive option for studying the diet [ 13 , 14 , 15 , 16 , 17 ]. Furthermore, advances in molecular techniques have increased the possibilities of faecal sampling as a powerful research tool for monitoring feeding habits, but also for targeting other aspects of wildlife biology [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%